Capitalismo dependente e governabilidade na América Latina: a herança dos regimes militares - Ayerbe, Luis Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 1993)
A trajetória do desenvolvimento do capitalismo latino-americano entre os anos 60 e 80 é analisada. Estudos de caso e problemas teóricos ligados à dependência, ao autoritarismo e à democracia são contemplados. Destaca-se a capacidade explicativa de algumas formulações teóricas, em contraste com a funcionalidade política de discursos pró-desenvolvimento com liberdade de mercado.

It is an analysis of the development of Latin American capitalism from the 60's to the 80's. Case studies, theoretical problems related to dependence, authoritarism and democracy are some of the focused aspects. It points out the explanatory capacity of some theoretical formulations that contrast with the political function of the speeches in favour of a free-market development.
Dependent capitalism and governability in Latin America: the military government heritage
Keywords: Dependência; Autoritarismo; Democracia; Mercado; Dependence; Authoritarism; Democracy; Markets